FOSTERING HUMAN DIMENSION OF SMART CITIES: Lessons from Jakarta for Nusantara, Indonesia’s New Capital City in the Making - Sarosa, Wicaksono; Susetyo, Nurulitha Andini; Aulianisa, Marsa Nur; Maulaa, Mahbub Ridhoo; Giffary, Pradamas (UI Scholars Hub, 2023)
A city’s problems often arise as the population grows and urbanization happens. This process is linear to the development of information-and-communication technologies (ICT), especially in urban areas. As a result, cities have adopted an initiative to solve the problems which are popularly known as the smart city. Over decades, the idea of a smart city has evolved from a mere technological modernization to advanced utilization through community involvement. However, in practice, smart city ideas and initiatives often put a heavy emphasis on technical aspects and ignored the more human side, which has caused a digital divide. This paper argues that centering the human perspectives in the smart city initiative is essential, and thus proposes an approach and its implementation measures to make an inclusive and smart Nusantara. Using systematic literature review and content analysis, the article attempts to explore human perspectives in smart city discourses as well as to analyze the gaps to do so. The proposed approach then applied in Indonesia's newest capital, which has the ambitious idea of making a smart world class city yet it still lacks attention to significantly address the human dimension in their smart city ecosystem. Therefore, our research suggests three recommended actions: improving equal access to ICT infrastructure, building digital literacy and capacity, and improving data security and protection efforts.